Implication of blood rheology and pulmonary hemodynamics on exercise-induced hypoxemia at sea level and altitude in athletes - Raberin, A.; Nader, E.; Lopez Ayerbe, J.; Mucci, P.; Pialoux, V.; Meric, H.; Connes, P.; Durand, F. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
This study aimed to investigate the changes in blood viscosity, pulmonary hemodynamics, nitric oxide (NO) production, and maximal oxygen uptake (VO2max) during a maximal incremental test conducted in normoxia and during exposure to moderate altitude (2,400 m) in athletes exhibiting exercise-induced hypoxemia at sea level (EIH). Nine endurance athletes with EIH and eight without EIH (NEIH) performed a maximal incremental test under three conditions: sea level, 1 day after arrival in hypoxia, and 5 days after arrival in hypoxia (H5) at 2,400 m. Gas exchange and oxygen peripheral saturation (SpO2) were continuously monitored. Cardiac output, pulmonary arterial pressure, and total pulmonary vascular resistance were assessed by echocardiography. Venous blood was sampled before and 3 min after exercise cessation to analyze blood viscosity and NO end-products. At sea level, athletes with EIH exhibited an increase in blood viscosity and NO levels during exercise while NEIH athletes showed no change. Pulmonary hemodynamics and aerobic performance were not different between the two groups. No between-group differences in blood viscosity, pulmonary hemodynamics, and VO2max were found at 1 day after arrival in hypoxia. At H5, lower total pulmonary vascular resistance and greater NO concentration were reported in response to exercise in EIH compared with NEIH athletes. EIH athletes had greater cardiac output and lower SpO2 at maximal exercise in H5, but no between-group differences occurred regarding blood viscosity and VO2max. The pulmonary vascular response observed at H5 in EIH athletes may be involved in the greater cardiac output of EIH group and counterbalanced the drop in SpO2 in order to achieve similar VO2max than NEIH athletes.